1998
DOI: 10.1146/annurev.arplant.49.1.427
|View full text |Cite
|
Sign up to set email alerts
|

BRASSINOSTEROIDS: Essential Regulators of Plant Growth and Development

Abstract: Brassinosteroids (BRs) are growth-promoting natural products found at low levels in pollen, seeds, and young vegetative tissues throughout the plant kingdom. Detailed studies of BR biosynthesis and metabolism, coupled with the recent identification of BR-insensitive and BR-deficient mutants, has greatly expanded our view of steroids as signals controlling plant growth and development. This review examines the microchemical and molecular genetic analyses that have provided convincing evidence for an essential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
790
1
12

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,266 publications
(812 citation statements)
references
References 123 publications
9
790
1
12
Order By: Relevance
“…Brassinosteroids (BRs), are naturally occurring plant steroid hormones found in a wide variety of plant species (Clouse and Sasse, 1998) are also involved in the control of germination in Arabidopsis. The BR signal leads to reduced sensitive to ABA and thereby stimulates germination, although the normal germination of BR deficient and BR signalling mutants indicates that there is no absolute BR requirement for germination (Steber and McCourt, 2001).…”
Section: Genes and Factors Affected In Seed Dormancy/germinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brassinosteroids (BRs), are naturally occurring plant steroid hormones found in a wide variety of plant species (Clouse and Sasse, 1998) are also involved in the control of germination in Arabidopsis. The BR signal leads to reduced sensitive to ABA and thereby stimulates germination, although the normal germination of BR deficient and BR signalling mutants indicates that there is no absolute BR requirement for germination (Steber and McCourt, 2001).…”
Section: Genes and Factors Affected In Seed Dormancy/germinationmentioning
confidence: 99%
“…This cold effect is mediated by a light stable bHLH transcription factor SPATULA (SPT), which suppresses the expression of these genes (Penfield et al, 2005). In addition cold may increase the sensitivity of seeds to GAs because it also has an effect in GA deficient mutants .The fact that often stratification is more effective than GA treatment (Alonso-Blanco et al, 2003) suggests that also other factors, promoting germination, are affected by stratification.Brassinosteroids (BRs), are naturally occurring plant steroid hormones found in a wide variety of plant species (Clouse and Sasse, 1998) are also involved in the control of germination in Arabidopsis. The BR signal leads to reduced sensitive to ABA and thereby stimulates germination, although the normal germination of BR deficient and BR signalling mutants indicates that there is no absolute BR requirement for germination (Steber and McCourt, 2001).…”
mentioning
confidence: 99%
“…Physiological studies have demonstrated that BR can induce diverse cellular responses such as stem elongation, pollen tube growth, leaf bending and epinasty, root inhibition, induction of ethylene biosynthesis and fruit ripening, and xylem differentiation [3][4][5][6]. The identification of Arabidopsis BR biosynthetic mutants established that BR is a new class of phytohormone with an essential role in plant growth and development [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…İlk olarak, 2,4-epi-brassinolide (eBR) in dışsal uygulamasının fasulye yapraklarında [48], salatalık kotiledonlarında [49] ve domates meyvalarında [50] senesensi teşvik ettiği gösterilmiştir. İkinci olarak, BR biyosentezi (örn; det2) ya da BR sinyal yolu (örn; bri1) eksik olan Arabidopsis mutantları gecikmiş yaprak senesensi fenotipi göstermektedirler [51]. bri1 fenotipini baskılayan bir mutasyon belirlenmiştir.…”
Section: Brassinosteroidlerunclassified